Shallow-water mussels (Mytilus galloprovincialis) adapt to deep-sea environment through transcriptomic and metagenomic insights - Luyang Sun; Xiaolu Liu; Li Zhou; Hao Wang; Chao Lian; Zhaoshan Zhong; Minxiao Wang; Hao Chen; Chaolun Li (Communications Biology)
Abstract Recent studies have unveiled the deep sea as a rich biosphere, populated by species descended from shallow-water ancestors post-mass extinctions. Research on genomic evolution and microbial symbiosis has shed light on how these species thrive in extreme deep-sea conditions. However, early adaptation stages, particularly the roles of conserved genes and symbiotic microbes, remain inadequately understood. This study examined transcriptomic and microbiome changes in shallow-water mussels Mytilus galloprovincialis exposed to deep-sea conditions at the Site-F cold seep in the South China Sea. Results reveal complex gene expression adjustments in stress response, immune defense, homeostasis, and energy metabolism pathways during adaptation. After 10 days of deep-sea exposure, shallow-water mussels and their microbial communities closely resembled those of native deep-sea mussels, demonstrating host and microbiome convergence in response to adaptive shifts. Notably, methanotrophic bacteria, key symbionts in native deep-sea mussels, emerged as a dominant group in the exposed mussels. Host genes involved in immune recognition and endocytosis correlated significantly with the abundance of these bacteria. Overall, our analyses provide insights into adaptive transcriptional regulation and microbiome dynamics of mussels in deep-sea environments, highlighting the roles of conserved genes and microbial community shifts in adapting to extreme environments.